Congenital cutaneous leishmaniasis. - Shelleh, H.H. (European Journal of Pediatric Dermatology, 2001)
We report about a case of cutaneous leishmaniasis in a seven months old child whose parents insisted that his lesion started since birth. The diagnosis was confirmed by histopathological examination. We think that this is the earliest cutaneous leishmaniasis involvement so far recorded.